IMPACT OF MENTAL HEALTH CARE FOR THE LGBTQIAPN+ POPULATION IN PUBLIC HEALTH SERVICES (PRÁXIS EM SAÚDE, 2025)
The LGBTQIAPN+ population faces discrimination and barriers in accessing healthcare. Although supported by public policies, there is a clear gap between what is established by law and what is observed in daily practice in public health services. In this context, the aim of this study is to identify, through a review, the impact of mental health care for the LGBTQIAPN+ population in public health services. The methodology used is a narrative literature review, considering studies published in journals over the past eight years. The search was conducted in the Virtual Health Library (BVS) databases: SCIELO, UESB, LILACS, PUBMED, and journals using keywords only in Portuguese (LGBTQIAPN+ Population, Minority Health, Social Vulnerability, and Gender), from which six articles were selected. Conclusion: There is a persistence of weaknesses in ensuring equitable and effective care in public health services, evidenced both by the lack of adequate training of professionals and by the limited implementation of public policies specifically aimed at the LGBTQIAPN+ population.
Keywords: Mental Health; Minority Health; LGBTQIAPN+ Population; Gender; Brazil